Collaborative driving tools for traffic problems: a design anthropological approach to car commuting (Research, Society and Development, 2022)
People use applications daily to meet some of their needs. Geo location, memory, communication, entertainment and learning are some examples, but it is well known that not every moment is suitable for the use of certain technologies, and sometimes its use is even illegal. While driving a car, a person tends to keep using their phones, even though it is distracting and dangerous, but the reasons behind this use are related to trying to make travel less unproductive and unpredictable. This problem leads this work to investigate the relationship between driving and the driver’s continuous interactions with technologies, focusing on a common identified activity: the informational collaboration, made from Geo location apps and instant messaging. For this, the Design Anthropology approach and the Design Ethnography method were used, seeking to understand how improvisations and contingencies can provide a deep understanding of the user's real needs. The results show that, by applying this methodology, it was possible to understand how and why people collaborate on traffic, including which applications they use and how they trust the information while adding their own personal knowledge.